EDUKASI PENYAKIT KECACINGAN PADA SISWA SDN 34 KOTA KENDARI: INFORMASI DAN PENCEGAHAN - Ilyas Y., Muhammad; Akib, Nur Illyyin; Jabbar, Asriullah; Halik, Halik; Masempo, Mustawakal; Aprilia, Sitti Aisyah; Yuqqabad, Yuqqabad; Erika, Erika; Pratiwi, Afryanti; Rusli, Nirwati; Badia, Esti; Nurhikma, Nurhikma (MAJU : Indonesian Journal of Community Empowerment, 2025)
Soil-transmitted helminthiases (STH) infections are one of the most common types of infections worldwide, with an estimated 1.5 billion people infected, accounting for 24% of the world's population. According to data from the WHO in 2024, more than 260 million pre-school children and 654 million school-aged children in Indonesia are vulnerable to helminthiasis infection. They are in urgent need of treatment and preventive interventions. Helminthiasis in children leads to a decline in their health and nutritional status, resulting in impaired growth, development, and physical and psychological activity. The purpose of this activity was to educate students of SD 34 Kendari class 3A about helminthiasis. This activity was carried out using the lecture method, providing leaflets and educational videos by lecturers, practitioners, and pharmacist professional students of the 13th batch of the Faculty of Pharmacy UHO, in collaboration with SDN 34 Kendari school, Puuwatu District, Kendari City. The results of this activity contributed to increasing the knowledge and understanding of students of SDN 34 Kendari about helminthiasis and how to prevent it.